Desktop-Based Office Stationery Management Information System Using Visual Basic at the Rancaekek DTP Health Center, Bandung Regency - Arini Alvi Oktavia; Husni Tamrin; Rina Kurniawati (Jurnal E-Komtek, 2022)
The management system at the Rancaekek DTP Health Center is still processed manually, so it is less effective and efficient. Officers are still experiencing difficulties in collecting data. The purpose of this research is to facilitate the management of office stationery. The result of this study is a desktop-based office stationery management information system application at the Rancaekek DTP Public Health Center in Bandung Regency. The data processing method in this study used qualitative and the waterfall software development method, with Analysis and Design tools using UML (Unified Modeling Language), language visual basic programming and Microsoft Access database. The developed application is informative. Login and password will ensure data confidentiality and an attractive interface. We hope this application can speed up the process of managing office stationery and reduce errors of using a manual system, so that reports can be properly accounted.